Partitioning of organic carbon among density fractions in surface sediments of Fiordland, New Zealand. Issue 3 (31st March 2016) - Cui, Xingqian; Bianchi, Thomas S.; Hutchings, Jack A.; Savage, Candida; Curtis, Jason H.
Abstract: Transport of particles plays a major role in redistributing organic carbon (OC) along coastal regions. In particular, the global importance of fjords as sites of carbon burial has recently been shown to be even more important than previously thought. In this study, we used six surface sediments from Fiordland, New Zealand, to investigate the transport of particles and OC based on density fractionation. Bulk, biomarker, and principle component analysis were applied to density fractions with ranges of <1.6, 1.6–2.0, 2.0–2.5, and >2.5 g cm −3 . Our results found various patterns of OC partitioning at different locations along fjords, likely due to selective transport of higher density but smaller size particles along fjord head‐to‐mouth transects. We also found preferential leaching of certain biomarkers (e.g., lignin) over others (e.g., fatty acids) during the density fractionation procedure, which altered lignin‐based degradation indices. Finally, our results indicated various patterns of OC partitioning on density fractions among different coastal systems. We further propose that a combination of particle size‐density fractionation is needed to better understand transport and distribution of particles and OC. Key Points: There are distinct patterns of OC partitioning on density fractions in Fiordland fjords Preferential leaching of OC during density fractionation impacts the use of biomarker proxies Partitioning of OC on density fraction in this study was compared with other coastal systems